Monetary policy, determinacy, and learnability in the open economy - James Bullard; Eric Schaling (European Central Bank (ECB), 2006)
We study how determinacy and learnability of global rational expectations equilibrium may be affected by monetary policy in a simple, two country, New Keynesian framework. The two blocks may be viewed as the U.S. and Europe, or as regions within the euro zone. We seek to understand how monetary policy choices may interact across borders to help or hinder the creation of a unique rational expectations equilibrium worldwide which can be learned by market participants. We study cases in which optimal policies are being pursued country by country as well as some forms of cooperation. We find that open economy considerations may alter conditions for determinacy and learnability relative to closed economy analyses, and that new concerns can arise in the analysis of classic topics such as the desirability of exchange rate targeting and monetary policy cooperation.
Keywords: E52; F33; 330; indeterminacy; international policy coordination; monetary policy rules; new open economy macroeconomics; Rationale Erwartung; Lernprozess; Mehr-Länder-Modell; Geldpolitik; Neoklassische Synthese; Wechselkurssystem; Theorie